The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3102/0002831219848691
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Justice, Justifying Practice: Toward Critical Practice Teacher Education

Abstract: Arguments for social justice teacher education and arguments for practice-based teacher education are often seen as incongruous. Drawing on sociocultural theory and theories of justice, our study interrogates this underresearched assumption. We conducted video analyses of teacher education coursework and novice teachers’ K–6 classroom instruction, together with novices’ written reflections on videos. Data were collected during a university-based, accelerated teacher credentialing program. Analyses of videos of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 65 publications
(87 reference statements)
1
30
0
1
Order By: Relevance
“…One reason for this may be that changing behavior is a trailing indicator. This is consistent with studies that have found that changes in attitudes toward equity take time and repetition to be successfully incorporated into teachers' behavior (Aronson et al, 2020;Cochran-Smith et al, 2016;Kavanagh & Danielson, 2020). Changes in behaviors are also mediated by what educators see around them (Battey & Franke, 2015;Woodcock & Woolfson, 2019); participants who were still in the beginning stages of changing their practice may have found it difficult to do so in schools where equity approaches to teaching were not broadly adopted.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…One reason for this may be that changing behavior is a trailing indicator. This is consistent with studies that have found that changes in attitudes toward equity take time and repetition to be successfully incorporated into teachers' behavior (Aronson et al, 2020;Cochran-Smith et al, 2016;Kavanagh & Danielson, 2020). Changes in behaviors are also mediated by what educators see around them (Battey & Franke, 2015;Woodcock & Woolfson, 2019); participants who were still in the beginning stages of changing their practice may have found it difficult to do so in schools where equity approaches to teaching were not broadly adopted.…”
Section: Discussionsupporting
confidence: 87%
“…Teacher education, like many other fields, has long been criticized for examining equity issues at a surface level, if they are addressed at all (Aronson et al, 2020;Cochran-Smith, 1995) Moreover, even when equity is explicitly discussed in teacher education, it is often disconnected from practice (Sleeter, 2012). For example, Kavanagh & Danielson (2020) studied a teacher education program focused on preparing educators to teach in urban environments with a specific focus on equity and social justice. The researchers found that while the faculty in the program explicitly modeled instructional techniques and provided opportunities for student practice, they rarely did so for equity issues.…”
Section: Linking Equity and Practice In Teacher Educationmentioning
confidence: 99%
“…Teacher educators have long struggled with how to create programming for teachers that bridges the gap between theory and practice and orients teacher education around the complexities and relational elements of teaching and learning to teach (Darling-Hammond, Hammerness, Grossman, Rust, & Shulman, 2005;Kavanagh & Danielson, 2020;Kazemi, Franke, & Lampert, 2009; McDonald, Kazemi, & Kavanagh, 2013;Zeichner, 2012).…”
Section: A Turn Toward Teacher Education-ambitious Teaching Core Practicesmentioning
confidence: 99%
“…Conklin and Hughes’s (2016) coding of their “compassionate, critical, justice-oriented” methods and curriculum courses, for example, found that their pedagogy incorporated representations more than decompositions and approximations. In another study, Kavanagh and Danielson (2019) analyzed video from their multicultural literacy methods course, finding that they employed pedagogies of enactment when teaching instructional practices but not when discussing issues of justice. Video analysis of novices’ instruction paralleled this, as most reflected on their instructional decisions through a frame of practice without attending to justice.…”
Section: Surfacing Divergence: Cpm’s Situated Critiques and Sjte’s Structural Critiquesmentioning
confidence: 99%